The Effect of Aerobic Training with Green Coffee on Body Composition and Lipid Profile in Overweight Women - Fariba Aghaei; Saeedeh Shadmehri; Zahra Pirbeyg Darvishvand (Islamic Azad University, 2018)
Introduction: Consumption of green coffee may play a protective role against various diseases in modern societies, such as obesity. The aim of this study was to investigate the effect of eight weeks of aerobic training with green coffee on body composition and lipid profile in overweight women. Methods: In this semi-experimental study, 30 overweight housewives were selected voluntarily and randomly divided into experimental (aerobic training-green coffee, 15 people) and control (aerobic training, 15 people) groups. Experimental (aerobic training-green coffee) and control (aerobic training) groups participated in the aerobic training program for 8 weeks, 3 sessions per week, 60 minutes each session with intensity of 70-80% of maximum heart rate. The subjects of the green coffee group daily consumed 90 mg of green coffee for 8 weeks. Data were analyzed with covariance analysis at p≤0.05. Results: Eight weeks of aerobic training and green coffee consumption had no significant effect on waist to hip ratio, body fat percentage, BMI, body mass, TG and HDL in overweight women (P>0.05). However, eight weeks of aerobic training and green coffee consumption significantly decreased cholesterol (P=0.001) and LDL (P=0.01) in overweight women. Conclusion: According to the findings of study, eight weeks of aerobic training and green coffee consumption caused a significant decrease in cholesterol and LDL in overweight women. Therefore, it can be said that probably aerobic exercise and green coffee consumption can reduce the harmful lipids in overweight individuals.